Organising as a catalyst for improving work conditions among informal quarry workers in Ghana. (17th October 2022) - Segbenya, Moses; Akorsu, Angela D.; Enu-Kwesi, Francis; Saha, Debdulal
Abstract : Organising has been suggested as one way to achieve decent working conditions among informal workers. This study examines how informal workers in Ghana are using organising as a catalyst for improving their working conditions. The study adopted an exploratory qualitative research design, using interviews, focus group discussions, documentary review and observation. Qualitative interpretative analysis methods were used to analyse the data. The study found that welfare-based organisations served as a catalyst for trade union organising among quarry workers. Despite the challenges confronting them in organising, informal quarry workers were able to improve their working conditions through a collective agreement with management. Specific indicators of work improvement included appointment letters for job security, hours of work and overtime, wages and salary (compensation), and training and development of workers to enhance their skills and competencies. The study concluded that organising informal workers served as a catalyst for ensuring decent working conditions among quarry workers in Ghana. This leads to the recommendation that formal trade unions organising in the quarrying districts should be resourced to be able to organise informal quarry workers in the stone quarry sub-sector of Ghana to achieve decent work conditions for informal workers in Ghana.